2004
DOI: 10.2165/00003088-200443120-00001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Interactions of Topiramate

Abstract: Topiramate is a new antiepileptic drug (AED) that has been approved worldwide (in more than 80 countries) for the treatment of various kinds of epilepsy. It is currently being evaluated for its effect in various neurological and psychiatric disorders. The pharmacokinetics of topiramate are characterised by linear pharmacokinetics over the dose range 100-800 mg, low oral clearance (22-36 mL/min), which, in monotherapy, is predominantly through renal excretion (renal clearance 10-20 mL/min), and a long half-life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(107 citation statements)
references
References 33 publications
4
98
2
3
Order By: Relevance
“…21,23) Enzyme induction by carbamazepine is associated with an approximately 2 to 3-fold increase in topiramate metabolic clearance. 7,10,22,24) It is interesting to note that in some studies in patients taking carbamazepine, topiramate renal clearance was also found to be significantly increased. 10,22) In contrast to carbamazepine, drug interaction with phenobarbital is considered as minor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…21,23) Enzyme induction by carbamazepine is associated with an approximately 2 to 3-fold increase in topiramate metabolic clearance. 7,10,22,24) It is interesting to note that in some studies in patients taking carbamazepine, topiramate renal clearance was also found to be significantly increased. 10,22) In contrast to carbamazepine, drug interaction with phenobarbital is considered as minor.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,10,[20][21][22][23][24] Carbamazepine significantly reduces topiramate concentration-to-dose ratio compared to topiramate monotherapy in both children and adults. 21,23) Enzyme induction by carbamazepine is associated with an approximately 2 to 3-fold increase in topiramate metabolic clearance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TPM is orally well absorbed with a bioabailability of 81∼95% [211] and there is a linear relationship between TPM dose and serum concentrations [212,213]. In three double-blind placebo-controlled add-on trials, seizure control was improved with serum TPM concentrations in the narrow range of 10 to 15 μmol/l and adverse events were also generally associated with higher TPM concentrations [214].…”
Section: Topiramate (Tpm)mentioning
confidence: 99%